Rat infestation associated with environmental deficiencies in an urban slum community with high risk of leptospirosis transmission - Norlan de Jesus Santos; Erica Sousa; Mitermayer G. Reis; Albert I. Ko; Federico Costa (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2017)
Abstract: We analyzed environmental factors that provide food, water and harborage to rodents and the risk of household rodent infestation in a slum community with a high risk of leptospirosis transmission. Detailed environmental surveys were performed in 221 households. Multivariate regression models evaluated the association between rodent infestation and socioeconomic status and environmental attributes obtained from Geographical Information System surveys. The general household infestation rate was 45.9%. Rattus norvegicus signs were the most prevalent, present in 74% of the infested households. The risk for rodent infestation was associated with environmental factors supporting harborage for rats, such as dilapidated fences/walls (OR: 8.95; 95%CI: 2.42-33.12) and households built on an earthen slope (OR: 4.68; 95%CI: 2.23-9.81). An increase of 1 meter from the nearest sewer was associated with a 3% (95%CI: 1%-5%) decrease in the risk of rodent infestation. A lack of sanitation where poor people live provides factors for rat infestation and could the target of educational interventions.